Peptidoglycan derived from Lacticaseibacillus rhamnosus and Lactobacillus acidophilus suppress TLR2/1-mediated inflammation in bovine endometrial epithelial cells - Waehama, Elham; Fukuda, Kenji; Mansouri, Alireza; Hulugalla, Malinda; Akthar, Ihshan; Yousef, Mohamed Samy; Miyamoto, Akio (Frontiers in Immunology, 2025)
Bacteria and associated products are factors in the pathogenesis of bovine endometrial inflammation, contributing to reproductive dysfunction. While peptidoglycan derived from Staphylococcus aureus (PGN-Sa) has been demonstrated to induce pro-inflammatory responses and disrupt sperm–immune interactions in bovine endometrial epithelial cells (BEECs) via Toll-like receptor 2/1 (TLR2/1), the immunomodulatory potential of peptidoglycan from lactic acid bacteria (LAB) within the female reproductive tract remains unexplored. This study investigated the in vitro immunomodulatory effects of LAB-derived peptidoglycan (PGN-L) on TLR2/1-mediated inflammation in BEECs, with the specific TLR2/1 agonist PAM3CSK4 (PAM3) as an inflammatory stimulus. PGN-L was extracted and characterized from Lacticaseibacillus rhamnosus (PGN-Lr) and Lactobacillus acidophilus (PGN-La), and its structural composition was compared to that of commercial PGN-Sa. Subsequently, BEECs were pre-incubated with PGN-L (Lr, La) or PGN-Sa (1 ng/mL) for 24 h before stimulation with PAM3 (100 ng/mL) for 3 h. The expression of inflammatory genes (TNF, CXCL8, IL1B, and PTGES) and TLRs (TLR1, TLR2, TLR4, and TLR6) was quantified by RT-qPCR. The protein expression of TNF, PTGES, and TLR2 was detected using immunofluorescence, while PGE2 concentrations in the culture media were measured by ELISA. PGN-Lr and PGN-La shared the GlcNAc-MurNAc backbone with PGN-Sa, while PGN-L had a unique modification. PGN-L and PGN-Sa contained lysine at the cross-bridge stem, composed of glycine in PGN-Sa and likely modified D-aspartate in PGN-L. While PGN-Sa and PAM3 significantly upregulated the expression of inflammatory mediators, neither PGN-Lr nor PGN-La alone induced a pro-inflammatory response in BEECs. Importantly, pretreatment with both PGN-Lr and PGN-La significantly reduced PAM3-induced inflammatory gene expression and reduced PGE2 secretion. In silico molecular findings suggested a potential mechanism whereby PGN-L may act as a TLR2/1 antagonist, contrasting with the agonistic effects of PGN-Sa and PAM3, which promoted TLR2/1 heterodimerization. These findings suggest that PGN-Lr and PGN-La can suppress TLR2/1-mediated uterine inflammation in vitro, by potentially modulating TLR2/1 signaling in BEECs. Further investigation of PGN-L holds promise for the development of therapeutic strategies to enhance bovine reproductive efficiency.